METODE LATIHAN DOUBLE LEG BOUND DAN DOUBLE LEG SPEED HOP UNTUK MENINGKATKAN POWER OTOT TUNGKAI ATLIT RENANG MATARAM - Maulidin Maulidin; Dadang Warta Chandra; Jamaludin Jamaludin (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2016)
Swimming is a very popular sport from all circles of society both for recreation and achievement. To obtain maximum swimming speed results, of course, needed muscle power, of the many muscle groups that play a role in the most dominant swimming movement of leg muscles. speed in swimming is influenced by the amount of muscle power of one's legs. Plyometric is a training with the characteristics of muscle contraction with full force as the response of the dynamic load and stretching of the muscles involved is a form of exercise to increase explosive powerThe aim of this research is to increase the muscle power of the athlete's limbs of Mataram swimming with two different exercises double leg bound plyometric exercises and double leg speed hop  exercise. This research  is an experiment research  with  Randomized  Control  Group  Pretest-Posttest  Design  research  design.  The sample of this study were 30 people divided into 3 groups selected at random. The data analysis technique used One way ANOVA analysis with the help of SPSS 17.0. The result of this research is based on the calculation of Paired Sampels Test The experimental group I where t count > t table or (14,024> 2,262) there is influence of doubel leg bound exercise to muscle limb muscle power for experimental group II obtained tcount > t table or (19.926> 2,262) it is concluded that there is influence of double leg speed hop exercise to muscle limb power of athlete swimming and for Group III (control group) Based on calculation result Paired Sampels Test obtained t count> t table or (1,516 <2,262) Then it can be concluded there is no influence because there is no given